PREVENTION OF CARDIOVASCULAR DISEASES IN CHILDREN - Mubinjonov Aziz Daminovich; Saidov Doniyorbek Olimjonovich; Asadov Muxammadullo Madilloyevich (Western European Studies, 2025)
Cardiovascular diseases (CVDs) are a leading cause of global morbidity and mortality, with their origins often traceable to childhood. Preventive strategies targeting pediatric populations can significantly reduce the long-term burden of CVD. This article provides a comprehensive examination of the epidemiology, risk factors, and evidence-based preventive approaches for CVD in children, focusing on modifiable factors such as obesity, hypertension, dyslipidemia, physical inactivity, and tobacco exposure. It explores primordial, primary, and secondary prevention strategies, emphasizing lifestyle interventions like the DASH diet, structured physical activity programs, and smoking cessation initiatives, supported by landmark studies such as the Bogalusa Heart Study and the Pathobiological Determinants of Atherosclerosis in Youth (PDAY). The article also addresses the role of early screening, multidisciplinary interventions, and community-based programs in mitigating CVD risk. In Uzbekistan, where urbanization and dietary shifts are increasing risk factor prevalence, culturally tailored strategies are essential. By fostering healthy behaviors from childhood, societies can reduce healthcare costs, improve quality of life, and promote cardiovascular health across generations.
Keywords: Cardiovascular disease; pediatric prevention; obesity